Seasonal Unit Root Tests under Structural Breaks - Uwe Hassler; Paulo M. M. Rodrigues (Technische Universität Darmstadt, Department of Law and Economics, 2002)
In this paper, several seasonal unit root tests are analysed in the context of structural breaks at known time and a new break corrected test is suggested. We show that the widely used HEGY test as well as an LM variant thereof are asymptotically robust to seasonal mean shifts of finite magnitude. In finite samples, however, experiments reveal that such tests suffer from severe size distortions and power reductions when breaks are present. Hence, a new break corrected LM test is proposed in order to overcome this problem. Importantly, the correction for seasonal mean shifts bears no consequence on the limiting distributions thereby maintaining the legitimacy of canonical critical values. Moreover, although this test assumes a breakpoint a priori, it is robust in terms of misspecification of the time of the break. This asymptotic property is well reproduced in finite samples. Based on a Monte Carlo study, our new test is compared with other procedures suggested in the literature and shown to hold superior finite sample properties.
Keywords: C12; C22; 330; Structural Breaks; Unit Roots; Seasonal Unit Root Tests; Unit Root Test; Strukturbruch; Theorie; Saisonbereinigung